FENOMENOLOGY GOING NEAR CONSTRUCTION OF CLASSIFICATIONAL UNTRADITIONAL RELIGIOUSNESS - Богдановський, І. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
In the article the basic going is examined near the construction of classification of untraditional religious organizations on the basis of the use of fenomenology methods of research.